“There Is Nothing I Can’t Face Now”: Coping With Child Loss Among Bereaved Parents in Ghana - Asare, G.O.; Yendork, J.S.; Annor, F. (OMEGA-Journal of Death and Dying, 2022)
Coping resources play a critical role in parents’ recovery from the trauma associated with child loss. In Ghana, little is known about how parents cope with child loss, despite the relatively high prevalence of child loss in the country. This study, therefore, sought to map out coping strategies bereaved parents adopt in response to child loss. Twenty Ghanaian parents were purposefully sampled and their accounts were thematically analyzed. Findings from the study show that bereaved parents adopted both cognitive and behavioral coping mechanisms. Religion and social support also emerged as useful coping resources for bereaved parents. Additionally, bereaved parents showed evidence of posttraumatic growth following child loss. The findings underscore the need for for practitioners to develop programs around adaptive coping methods that bereaved parents are familiar with to enhance their chances of developing progressive outcomes in the course of managing the distress associated with child loss.
Research Article
Keywords: child loss; posttraumatic growth; coping